Autoimmune thyroid disease modifies the clinical expression of hand osteoarthritis in older people: a third National Health and nutrition examination survey study - Tagoe, Clement E.; Wang, Wanyi; Kwon, Helena H. (Frontiers in Medicine, 2024)
The risk factors linked to hand osteoarthritis (OA) that contribute to its distinct symptoms and clinical presentation are not thoroughly understood. This study aimed to examine whether the autoimmune thyroid disease (AITD) autoantibodies, anti-thyroid peroxidase antibody (TPOAb) and anti-thyroglobulin antibody (TgAb), associate with hand OA and symptomatic hand OA in the Third National Health and Nutrition Examination Survey (NHANES III).We included 2429 persons from NHANES III ≥60 years of age. Data on hand OA or symptomatic hand OA were examined with respect to their associations with TPOAb and TgAb. Log binomial and modified Poisson regression models were fit to examine the associations between the anti-thyroid autoantibodies, and hand OA or symptomatic hand OA.Results: Higher levels of TPOAb were associated with a higher prevalence of symptomatic hand OA in the unadjusted (PR=1.182, p=0.024) and adjusted models, after controlling for age, gender, and diabetes (PR=1.174, p=0.039). This association was no longer significant when positive TPOAb was considered as a categorical variable with four levels and compared with negative TPOAb. TgAb showed a trend to being positively associated with symptomatic hand OA (p<0.10). When positive TgAb was considered as a categorical variable with four levels and compared with negative TgAb the highest quartile was associated with a higher prevalence of symptomatic hand OA than negative TgAb in the unadjusted (PR=2.242, p=0.008) and adjusted models (PR=2.045, p=0.038). There was no significant association between TPOAb or TgAb and hand OA.